The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1057/s41287-017-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Poor Children in Rich Households and Vice Versa: A Blurred Picture or Hidden Realities?

Abstract: An expanding evidence base suggests that children experiencing monetary and multidimensional poverty are not the same. This article breaks new ground by providing a unique mixed methods investigation of drivers of child poverty mismatch in Ethiopia and Vietnam, considering the role of measurement error and individualistic and structural factors. The analysis capitalises on large-scale secondary quantitative panel data and combines this with purposively collected primary qualitative data in both countries. It f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Even though poverty has traditionally been associated with the lack of a certain income, there is a growing literature discussing the theoretical and methodological shortcomings of monetary vis-àvis nonmonetary approaches (Bourguignon and Chakravarty 2003;Roelen and Gassmann 2008;Roelen 2018). If we were to draw the different approaches to poverty on one "welfare measurement continuum," we would have something similar to Fig.…”
Section: Approaches To the Measurement Of Multidimensional Povertymentioning
confidence: 99%
“…Even though poverty has traditionally been associated with the lack of a certain income, there is a growing literature discussing the theoretical and methodological shortcomings of monetary vis-àvis nonmonetary approaches (Bourguignon and Chakravarty 2003;Roelen and Gassmann 2008;Roelen 2018). If we were to draw the different approaches to poverty on one "welfare measurement continuum," we would have something similar to Fig.…”
Section: Approaches To the Measurement Of Multidimensional Povertymentioning
confidence: 99%
“…We analyse the impact of the Lesotho Child Grant (CGP) on a multidimensional index of deprivation for school-aged children, and we operationalize the concept of child poverty using a rights-based approach (Gordon et al, 2003;de Neubourg et al, 2012). We use a measure of multidimensional deprivation to assess children's wellbeing, as it is increasingly recognized that household-based measures of monetary poverty do not necessarily capture children's experiences of deprivation in areas key to their development and well-being (Roelen and Gassmann 2008;Roelen 2018). Furthermore, evidence shows how children in rural areas are consistently more deprived than children in urban areas, even when their families are not monetarily poor (UNICEF Malawi, 2016, UNICEF Tanzania, 2016 The CGP is a large-scale national unconditional CT programme targeted to reach the poorest households with children.…”
Section: Introductionmentioning
confidence: 99%
“…Roelen (2017) found that overlap between monetary and multidimensional child poverty is least, which suggests both the measure capture types of poverty. In another study, Rolen (2018) found that individual-level factors are important determinates for the gap between monetary and multidimensional child poverty measures. In this background, the paper measures the extent of child poverty in Indian states by following the modified Bristol method and the multidimensional poverty approach and compares the result with monetary poverty.…”
Section: Introductionmentioning
confidence: 99%